Performance of Al-Air Battery with Different Electrolytes - Maárif , Mochammad Syamsul; Fanani, Ardiansyah Zeen; Oerbandono, Tjuk; Wardana, Bayu Satria (International Journal of Integrated Engineering, 2021)
Aluminium-air battery is a type of battery that offers high energy density (up to 8.1 kWh/kg) with a theoretical voltage of 2.71 V. Because of the high energy density and versatility, the battery attracts many users. Similar to other batteries, it consists of electrodes and electrolytes. The study aims to investigate the voltage generated by the battery when different electrolytes are employed. Since different electrolytes discharge different amounts of electron charge, the voltage will also differ from one to another. It also holds true when different pH of electrolyte is used. Using NaCl with a pH of 7, NaOH a with pH of 11 and KOH with a pH of 14, the investigation shows that increasing the level of pH results in a higher generated voltage but has the side effect of making Al more easily dissolved into the electrolyte. For the electrolyte which is considered neutral, i.e. NaCL, the lifetime of the battery was the longest as shown by the stability of the generated voltage compared to the other two electrolytes. NaOH and KOH which are categorized as strong bases showed a considerable decrease in generated voltage during the investigation.